Study of Rumen Ciliates from Indian Goat (Capra hircus) - Nath, Deblina; Chowdhury, Suchandra (Asian Journal of Biological and Life Sciences)
The gut microbiome of rumens is composed of a wide diversity of bacteria, fungi and protozoa. The rumen protozoa were first described by Gruby and Delafold in 1842 and seemed to have importance in the metabolism of the host. In this study, we report the presence of twelve different species of ciliates from the ruminant content of the Indian goat (Capra hircus) from West Bengal, India. These ciliates can be grouped under four genera namely Entodinium, Diplodinium, Epidinium and Eremoplastron. In the genus Entodinium, the nine species identified were E. dubardi, E. nanellum, E. simplex, E. loboso-spinosum, E. exiguum, E. parvum, E. rupicaprae, E cervi and E. leave. In genus Diplodinium, the species identified were D. costatum while in the other two genera the species identified were Epidinium ecuadatum and Eremoplastron impalae. Eremoplastron impalae were the largest ciliates among the studied populations while Entodinium exiguum were the smallest. In this study, some ciliates like Entodinium exiguum are reported from Capra hircus of West Bengal for the first time while others like Entodinium parvum, Entodinium rupicaprae, Entodinium cervi, Epidinium ecuadatum, Eremoplastron impalae were exclusively reported in the rumen content of Indian Goat for the first time in this study.
Keywords: Camera lucida; Capra hircus; Entodinium sp.; Eremoplastron sp; Micrometry; Rumen ciliates